2013
DOI: 10.1016/j.jaac.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Microstructure in Subjects With Attention-Deficit/Hyperactivity Disorder and Their Siblings

Abstract: Objective Previous voxel-based and regions-of-interest (ROI)-based diffusion tensor imaging (DTI) studies have found above-normal mean diffusivity (MD) and below-normal fractional anisotropy (FA) in subjects with attention-deficit/hyperactivity disorder (ADHD). However, findings remain mixed and few studies have examined the contribution of ADHD familial liability to white matter microstructure. Method We used refined DTI tractography methods to examine MD, FA, axial diffusivity (AD) and radial diffusivity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
64
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 56 publications
14
64
1
1
Order By: Relevance
“…In regard to weaknesses on tasks measuring attentional control, working memory, and cognitive processing and response speed, the NF1 IQ profile is in keeping with research on other developmental disabilities, showing a consistent susceptibility to disruption in attention, working memory, and cognitive efficiency functions (Oliveras-Rentas et al 2011;Mayes and Calhoun 2006). These types of neuropsychological deficits are linked to disruptions in white matter tracts, which are particularly vulnerable due to their protracted developmental trajectory (e.g., Barnea-Goraly et al 2005) and are commonly seen in developmental disabilities including NF1, ADHD, and autism spectrum disorders (ASD) (e.g., Lawrence et al 2013;Weinstein et al 2011;Cutting et al 2002). From this perspective, the IQ profile seen in children with NF1 reflects similar vulnerabilities as those observed in other developmental disabilities, such as ADHD and ASD.…”
Section: Impairment Levelssupporting
confidence: 73%
“…In regard to weaknesses on tasks measuring attentional control, working memory, and cognitive processing and response speed, the NF1 IQ profile is in keeping with research on other developmental disabilities, showing a consistent susceptibility to disruption in attention, working memory, and cognitive efficiency functions (Oliveras-Rentas et al 2011;Mayes and Calhoun 2006). These types of neuropsychological deficits are linked to disruptions in white matter tracts, which are particularly vulnerable due to their protracted developmental trajectory (e.g., Barnea-Goraly et al 2005) and are commonly seen in developmental disabilities including NF1, ADHD, and autism spectrum disorders (ASD) (e.g., Lawrence et al 2013;Weinstein et al 2011;Cutting et al 2002). From this perspective, the IQ profile seen in children with NF1 reflects similar vulnerabilities as those observed in other developmental disabilities, such as ADHD and ASD.…”
Section: Impairment Levelssupporting
confidence: 73%
“…[31][32][33] Despite the lack of change of the cingulum bundle property in individuals with ADHD reported in our prior investigation 23 and in another study 32 with a much larger independent sample and a different DSI tractography approach from our earlier investigation, current studies support decreased diffusion anisotropy of the cingulum bundle in youths with ADHD.…”
Section: Alteration Of White Matter Microstruactual Propertycontrasting
confidence: 69%
“…Casey et al (2007 showed that disruption in fronto-striatal fiber tracts of subjects with ADHD was correlated with lower performance on a go/no go task, suggesting atypical fronto-striatal circuitry affects cognitive control in children with ADHD. Importantly, some of these findings are strengthened by work showing their heritability (Casey et al 2007;Lawrence et al 2013). In a sibling study by Lawrence et al (2013), individuals with ADHD and their unaffected siblings show similar differences in white matter microstructure, compared to controls, in the anterior thalamic radiation, forceps minor, and superior longitudinal fasciculus.…”
Section: Structural Changes Measured With Dti In Typical Development mentioning
confidence: 94%